TINGKAT PENDAPATAN DALAM HUBUNGAN DENGAN DISTRIBUSINYA DIANTARA RUMAHTANGGA PEDESAAN - A. Rozana Nurmanaf (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2005)
Level of income is usually used as the indicator of economic development successful. But, increasing in income is not always followed by the improvement of its distribution. The purpose of this paper is to examine interrelationship between level of income and skewed level of its distribution among households. By using data Patanas ( National Panel of Farmer Study) done by Puslitbang Sosek Pertanian 2004, relationship analysis has been done between income per head and Gini Coefficient as the measurement of skewed level of income distribution. The result show a complete stage of economic development, these are first stage and next stage. In the first stage, income and welfare society distribution tend to skewer together with increasing level of income and economic development successful. Modern sector of economy with just a few actors contributes larger income to society. Whie, traditional sector of economy contributes ust small income yet a lot of actors involve. In the next stage , development successful increase income level and society welfare skewed level. The improvement of traditional sector contributes larger income than modern sector that also improves especially in the number of its actors.